The Creativity Development of Finger Painting to Stimulate Cognitive, Affective, and Motoric of Early Childhood - Rosdiana, Aliva; Pratiwi, Dewi (Program Studi Pendidikan Agama Islam (PAI), 2023)
The purpose of this study is to investigate children's cognitive, affective, and motor development through creativity of finger painting art. The stimulation of these three aspects of Bloom's taxonomy teaches children to recognize colors and to apply cognitively, teaches children to practice patience affectively, and teaches children to use their fingertips to stimulate their motor development through finger muscles. This study used a qualitative method with a case study design to 25 early childhood students aged 5-7 years old at TK Pertiwi Bacin Kudus. Data collection techniques used observation, interviews, and documentation. According to Permendikbud about National Standards for Early Childhood Education, the assessment criteria used are underdeveloped (UD), beginning to develop (BD), very well developed (VD), and develop as expected (DE). The data observed indicates BD before students got finger painting activities. The results of the study obtained 3 aspects based on Bloom’s taxonomy. From those aspects of development, the highest percentage of cognitive aspect was 72% in BD. The result illustrated that 18 children began to mention colors. The highest aspect of affective was 64% in BD. It indicates that 16 children ask for help to the process and technique of finger paintings. They ran to go through the process and steps to DE. The highest aspect of psychomotor was 60%. It describes that 15 children began to develop when they smeared colors unclearly bright to form object.